Fernando González Ollé, El habla de La Bureba. C.S.I.C., Madrid, 1964; 258 pp. (RFE, anejo 78). - Garza Cuarón, Beatriz (Nueva Revista de Filología Hispánica (NRFH), 1970)
Se reseñó el libro: El habla de La Bureba.